Intraoperative evaluation of big-endothelin plasma levels during liver transplantation in different vascular compartments - Kraus, Thomas W.; Mehrabi, Arianeb; Klar, Ernst; Arnold, J.; Sido, Bernd; Otto, Gerd; Herfarth, Christian (Transplant international, 1994)
Endothelin-1 (ET) is derived from its precursor big-ET, secreted by endothelial cells of multiple origin. The role of ET peptides in the physiological responses after orthotopic liver transplantation (OLT) was investigated. Venous big-ET plasma levels were analysed by RIA in 28 patients before and after OLT. Samples for analysis were taken intraoperatively from 12 patients from the caval, portal and hepatic veins and the radial artery at multiple time points. Highest caval levels were found during the an-hepatic period and 60 min after reperfusion, followed by a drop and subsequent increase postoperatively. Highest levels in the hepatic and portal veins were detected during explanation and reperfusion. A different pattern was found in the radial artery. Values during rejection and infection were elevated compared with preoperative and postoperative levels. The heterogeneity of the kinetics points to different sites of ET generation, including liver and splanchnic circulation. It suggests a predominant paracrine secretion mode of ET peptides with various stimuli involved. Big-ET levels could reflect endothelial cell damage, as big-ET is generated intracellularly and biological activity is rather weak.